THEORETICAL ASPECTS OF EDUCATIONAL TOURISM - Stivriņa, Karina; Ļubkina, Velta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
In today's technological era, rural tourism with its unique and unusual offer, which carries the traditions, culture and culinary heritage of ancestors, becomes a proper and unique cultural capital, and it has opportunities to hybridize with other types of tourism, for example, with educational tourism. As a separate type of tourism - educational tourism, becomes an innovative opportunity to revive the usual rural tourism offer. In order to retain the interest of tourists, the tourism experience must have transformative potential. Consumer experiences can contribute to tourists' cognitions and emotions, resulting in psychological, physical, social, or knowledge changes. Educational tourism combines the features of two fields: education and tourism, which at the intersection gives the actual educational tourism. In Latvia, educational tourism is not defined as a separate economic category. This type of tourism can become a successful platform for travelers' self-growth, creating opportunities for them to learn, relax and improve spiritually. The aim of the study is to analyze the interpretations of the definition. The research uses the scientific literature research method. The research questions are (1) What research has been done on aspects of educational tourism? (2 ) Which scientists have focused on the study of this concept? (3) What are the prerequisites for the introduction of educational tourism in Latgale/regions? An exploratory study was implemented and described in this paper.